WORK STRESS AND EMPLOYEE PERFORMANCE AT THE LAMPUNG PROVINCIAL LEGISLATIVE SECRETARIAT - Yusmanto; Ida Farida (International Journal of Multidisciplinary Reseach, 2026)
Public-sector employees face increasing performance demands alongside bureaucratic reform, digitalization, and the dynamic political agendas of legislative institutions. This study analyzes the formation of work stress, its implications for employee performance, and the organizational factors that inhibit or support stress management at the Lampung Provincial DPRD Secretariat. A qualitative descriptive-analytical design was employed. Data were collected from April to June 2026 through in-depth interviews, passive participant observation, and analysis of performance, attendance, meeting-agenda, and accountability documents. Informants were selected purposively and expanded through snowball sampling until data saturation. The findings show that work stress develops through the interaction of environmental stressors, organizational demands, and individual pressures. Work overload, role conflict, rigid procedures, work-family conflict, and technostress move employees beyond the optimal eustress zone toward distress. The resulting physiological, psychological, and behavioral symptoms reduce concentration, motivation, document accuracy, coordination, and decision quality. Peer support and individual resilience function as protective resources, while the absence of mental-health policies, unsupportive leadership, and stigma constrain effective management. Workload redistribution, adaptive procedures, supportive leadership, and formal employee-assistance services are therefore recommended.